The Autonomic and Nociceptive Response to Acute Exercise Is Impaired in People with Knee Osteoarthritis - Bossenger, NR; Lewis, GN; Rice, DA; Shepherd, D (Elsevier BV, 2023)
Objectives An acute bout of exercise typically leads to short term exercise induced hypoalgesia (EIH), but this response is more variable in many chronic pain populations, including knee osteoarthritis (OA) and fibromyalgia (FM). There is evidence of autonomic nervous system (ANS) dysfunction in some chronic pain populations that may contribute to impaired EIH, but this has not been investigated in people with knee OA. The aim of this study was to assess the acute effects of isometric exercise on the nociceptive and autonomic nervous systems in people with knee OA and FM, compared to pain-free controls. Methods A cross-sectional study was undertaken with 14 people with knee OA, 13 people with FM, and 15 pain free controls. Across two experimental sessions, baseline recordings and the response of the nociceptive and autonomic nervous systems to a 5-min submaximal isometric contraction of the quadriceps muscle was assessed. The nociceptive system was assessed using pressure pain thresholds at the knee and forearm. The ANS was assessed using high frequency heart rate variability, cardiac pre-ejection period, and electrodermal activity. Outcome measures were obtained before and during (ANS) or immediately after (nociceptive) the acute bout of exercise. Results Submaximal isometric exercise led to EIH in the control group. EIH was absent in both chronic pain groups. Both chronic pain groups showed lower vagal activity at rest. Furthermore, people with knee OA demonstrated reduced vagal withdrawal in response to acute isometric exercise compared to controls. Sympathetic reactivity was similar across groups. Discussion The findings of reduced tonic vagal activity and reduced autonomic modulation in response to isometric exercise raise the potential of a blunted ability to adapt to acute exercise stress and modulate nociception in people with knee OA. The impairment of EIH in knee OA may, in part, be due to ANS dysfunction.
Keywords: Knee osteoarthritis; Fibromyalgia; Autonomic nervous system; Exercise-induced hypoalgesia; Pressure pain threshold; Isometric exercise